Investigation of viscosity of R123-TIO 2 nanorefrigerant - Mahbubul, I.M.; Saidur, Rahman; Amalina, M.A. (International Journal of Mechanical and Materials Engineering, 2012)
Nanorefrigerant is one kind of nanofluids. It is the mixture of nanoparticles with refrigerants. It has better heat transfer performance than traditional refrigerants. Recently, some researches have been done about nanorefrigerants. Most of them are related to thermal conductivity of these fluids. Viscosity also deserves as much consideration as thermal conductivity. Pumping power and pressure drop depends on viscosity. In this paper, the volumetric and temperature effects over viscosity of R123-TiO 2 nanorefrigerants have been studied for 5 to 20Â°C temperature and up to 2 vol. . The effect of pressure drop with the increase of viscosity has also been investigated. Based on the analysis it is found that viscosity of nanorefrigerant increased accordingly with the increase of nanoparticle volume concentrations and decreases with the increment of temperature. Furthermore, pressure drop augmented significantly with the intensification of volume concentrations and vapor quality. Therefore, low volume concentrations of nanorefrigerant are suggested for better performance of a refrigeration system.